Handbook of Strategic Alliances. - Shenkar, Dr. Oded (SAGE Publications, 2005)
The Handbook of Strategic Alliances covers state-of-the-art research on strategic alliances and serves to pave the road for future alliance research. Little is understood about the specific managerial challenges involved in establishing and operating alliances from their initial setup and throughout their life cycle. The Handbook is intended to fill this gap by looking inside some of the "black boxes" that have been acknowledged in the alliance literature but seldom opened. Leading scholars and practitioners from around the globe chart the alliance literature, its evolution, current state, and.